2017
DOI: 10.1097/pec.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Adolescent Binge Drinking at Lollapalooza, A Music Festival in Chicago

Abstract: Objectives Lollapalooza (LP) is an annual 3-day outdoor music festival in Chicago. Underage drinking and drug use are believed to be common, but the burden on emergency departments (EDs) has not been documented. We assessed the burden on health care resources associated with this music festival. Methods We performed a retrospective chart review of adolescent (aged 11–20 years) ED visits during LP weekend and 4 summer comparison weekends at Lurie Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In another study of a large music festival, it was shown that heat-related patient presentations increased with average temperature [ 30 ]. Lack of rest/sleep (and eating) due to multiple days of attending also appears to increase risk of adverse outcomes, and those who travel to festivals outside of their home area are also at high risk for adverse drug outcomes [ 4 , 31 , 32 ]. Given these cases, adequate medical response to emergencies at festivals is critical.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of a large music festival, it was shown that heat-related patient presentations increased with average temperature [ 30 ]. Lack of rest/sleep (and eating) due to multiple days of attending also appears to increase risk of adverse outcomes, and those who travel to festivals outside of their home area are also at high risk for adverse drug outcomes [ 4 , 31 , 32 ]. Given these cases, adequate medical response to emergencies at festivals is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst previous literature has reviewed the care of children at music festivals, very little is published on the under 10 years age group. 3 , 34 Despite this paper providing insight into the varying care required by these two subpopulations, the small numbers of these patients make it challenging to draw any firm conclusions. Similar music festivals which are attended by young children and guests over the age of 65 should now be evaluated to determine if similar results are uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…With this study's design and methods, we combined metabolic assessments in our research facilities with a 'real life' intervention at a festival site. To our knowledge, previous studies of festival attendees have not investigated the immediate metabolic consequences but rather focused on drug-and alcohol-related emergencies (21,22,23,24). It was not possible to gather the festival participants on the day they left the festival site since they left at varying time points and in different conditions.…”
Section: Discussionmentioning
confidence: 99%